Bridging the gap between academic and industry Li-ion battery research - Ha, Yeyoung; Licht, Rachel B.; Bogart, Timothy D.; Beers, Keith M. (Frontiers in Batteries and Electrochemistry, 2024)
The field of lithium (Li)-ion batteries has entered a stage where industry is largely focusing on optimizing current cell chemistries to increase the effective energy density of commercial cells while academia is mainly driven by the development of novel materials for next-generation cell chemistries. In addition to their different research goals, industry is producing commercial cells with increasingly diversified size and shape, while the majority of academic research reports on limited small sized cell formats. Such differences in research settings are leading to a disconnect between industrial and academic perspectives. More specifically, a disconnect arises due to academic research results obtained from smaller scale cells not translating to cells with more complex designs. In this paper, we discuss where a disconnect between industry and academia exists, and demonstrate how industry relevant problems can be studied in academia by utilizing a multifaceted approach and further provide valuable insights at a practical level.